Model-based distributed object computing. (c2002) - Hage, Antoine F. (2002)
Four trends are shaping the future of commercial software development. First, the software industry is moving away from programming applications from scratch to integrating applications using reusable components. Second, there is great demand for distribution technology that provides remote method invocation and/or message-oriented middleware to simplify application collaboration. Third, there are increasing efforts to define standard software infrastructure frameworks that permit applications to interwork seamlessly throughout heterogeneous environments. Finally, next-generation distributed engineering modeling applications require quality-of-service (QoS) guarantees for latency, bandwidth, and reliability. A key software technology supporting these trends is distributed object computing (DOC) middleware. DOC middleware facilitates the collaboration of local and remote application components in heterogeneous distributed environments. The goal of DOC middleware is to eliminate many tedious, error-prone, and nonportable aspects of developing and evolving distributed applications and services. At the heart of DOC middleware are Object Request Brokers (ORBs), such as CORBA, DCOM, and Java RMI This thesis describes how the DOC concept was used to create a new Model-based Distributed Object computing (MDOC) technology that creates a robustness object oriented environment to optimize and automate modeling through the Intranet / Internet. In particular this document will describe the architecture, security layers, connectivity, and the client/server application of MDOC.